Ectodermal dysplasias: Classification and organization by phenotype, genotype and molecular pathway - Wright, John Timothy; Fete, Mary; Schneider, Holm; Zinser, Madelaine; Koster, Maranke I.; Clarke, Angus J.; Hadj-Rabia, Smail; Tadini, Gianluca; Pagnan, Nina; Visinoni, Atila F.; Bergendal, Birgitta; Abbott, Becky; et al. (American Journal of Medical Genetics Part A, 2019)
An international advisory group met at the National Institutes of Health in Bethesda, Maryland in 2017, to discuss a new classification system for the ectodermal dysplasias (EDs) that would integrate both clinical and molecular information. We propose the following, a working definition of the EDs building on previous classification systems and incorporating current approaches to diagnosis: EDs are genetic conditions affecting the development and/or homeostasis of two or more ectodermal derivatives, including hair, teeth, nails, and certain glands. Genetic variations in genes known to be associated with EDs that affect only one derivative of the ectoderm (attenuated phenotype) will be grouped as non-syndromic traits of the causative gene (e.g., non-syndromic hypodontia or missing teeth associated with pathogenic variants of EDA "ectodysplasin"). Information for categorization and cataloging includes the phenotypic features, Online Mendelian Inheritance in Man number, mode of inheritance, genetic alteration, major developmental pathways involved (e.g., EDA, WNT "wingless-type," TP63 "tumor protein p63") or the components of complex molecular structures (e.g., connexins, keratins, cadherins).
CRIS-Team WoS Importer:2019-02-27